Tunable 2D Nanomaterials; Their Key Roles and Mechanisms in Water Purification and Monitoring - Fatima, Jawaria; Shah, Adnan Noor; Tahir, Muhammad Bilal; Mehmood, Tariq; Shah, Anis Ali; Tanveer, Mohsin; Nazir, Ruqia; Jan, Basit Latief; Alansi, Saleh (Frontiers in Environmental Science, 2022)
Water supplies around the world are currently heavily polluted by heavy-metal chemicals, synthetic dyes, and other toxic pollutants released by major factories rather than typical household waste. This pollution necessitates adequate monitoring to protect natural water sources. There are various wastewater treatment methods available, including nanotechnology, i.e., two dimensional (2D) nanomaterials. Rising 2D nanomaterials including graphene, g-C3N4, MoS2, MXene, black phosphorus, and h-BN have exhibited an unparalleled surface-to-volume ratio, promising ultralow usage of material, ultrafast handling time, and ultrahigh treatment performance for cleaning, and monitoring of water. We provide a current overview of tunable 2D nanomaterials and their uses in water management. A brief description of 2D nanomaterials, their types, synthesis strategies and salient features involved in water management is provided. Furthermore, application of 2D nanomaterial in different processes of water treatment such as pollutants adsorption, filtration, disinfection, photocatalysis are discussed in detail. Likewise, the potential of 2D nanomaterials to be used in water quality monitoring gadgets like fluorescent sensors, colorimetric sensors, electrochemical sensors, and field-effect transistors are also explored. The study ends with a look at the current problems, limitations and future prospectus associated with the use of 2D material in water management. The importance of clean and fresh water to upcoming generations will bring new light and innovations to this emerging sector, allowing it to improve the quality and accessibility of water treatment while also ensuring global water supplies in an increasing part of the world.